STRUCTURAL SEARCH CODES FOR ONLINE COMPOUND REGISTRATION - Evans, L; Lynch, M; Willett, P (1978)
A topological index has been developed which can discriminate between isomers in a molecular formula group. This index could be used, in combination with the molecular formula, to provide rapid access to those few compounds in a large chemical structure file which must be compared with a query structure at registration. © 1978 American Chemical Society.